Knowledge and Compliance to Healthy Ageing Promotion Practices Among Rural and Urban Adult Population in Rivers State - Okankwu, Elizabeth Amini; Robinson-Bassey, Grace Chinyere; Emordi, Nnenna Ali; Okankwu, Judy Chidinma (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
This study aimed to compare the knowledge and compliance indices of healthy ageing promotion practices among rural and urban adult populations in Rivers State, Nigeria. A comparative research design was conducted among 597 participants, comprising of 299 rural and 298 urban dwellers, using a structured 30-item questionnaire two subsections with reliability coefficients of 0.75 and 0.81 for knowledge and compliance indices of healthy ageing promotion practices respectively using the test re-test method. Three research questions and three hypotheses guided the study. The data collected were analyzed using descriptive statistics, independent samples t-test, and regression analysis. The study found that there was no significant difference in the knowledge and compliance indices between rural and urban populations. However, there was a weak positive correlation between knowledge and compliance indices in both populations. The study recommends among others that health education programmes be developed to increase knowledge and compliance with healthy ageing promotion practices in both rural and urban populations.